Determinants of Bursa Malaysia Stock Market Returns amid the Fourteenth General Election - Liew, Venus Khim Sen; Rowland, Racquel (HRMARS, 2020)
This study attempts to examine the effect of the Fourteenth General Election on the market returns in Malaysia. It is found that the election effect lasted for 30 days of trading window and the stock market managed to price-in the election news since then. Secondly, market volatility which represents political uncertainty continued to play significant role in determining stock market return, as were in the previous two general elections. Nonetheless, market volatility had adverse effect, and as such Bursa Malaysia might not fulfil the appetite of those investors who demand higher return for higher risks amid election year. In addition, this study for the first time reveals fairly low but significant market integration between Malaysia and US stock market around the general election year. This signifies that apart from domestic political issues and macroeconomic performances amid general election event, investors in Bursa Malaysia need to closely monitor global issues that would affect the US stock market and hence the performance of Bursa Malaysia.